TRAINING RENOVASI DAN PERAWATAN POMPA HIDRAM DI DESA KARANG PELEM, KECAMATAN KEDAWUNG, SRAGEN - Aliem Sudjatmiko; Qunik Wiqoyah; Mohammad Ujianto (WARTA LPM, 2007)
Technological Pump the Hidram technology pump to use the basework style of grafitasi earth and designed in such a way till work the pumpwork automatically without there external energi for example energi oil.Constraint which often bother the [job/activity] pump the hidram  is notoptimal is component function pump the effect stuffing up of dirt andcomponent damage pump. The pump Hidram equiped some kinds ofspillway, for example functioning water spillway to arrange awaking ofcurrent and awaking of pressure irrigate the , air-trap to arrange awakingof air composition in water. Especial benefit air good for condition of[isnature of water from nature of water which incompresible become semiincompresible so that punching influence irrigate the/hummer water notdestroy the material pump specially save the tekan.Tabung depress tofunction to catch and maintain the yielded water pressure. Component pumpthe hidram consisted of the Reservoir concentration, fast pipe, spillway oflimbah,balance weight, air spillway, spillway depress and save to depressand also other supporter that is pipe between. In course of evaluation[done/conducted] repair problem of water spillway using rubber of vehiclerut/rubber konveyor, and if/when reckoned from a economic side pumpthis very efficient because energi used to create the pressure irrigate tocome from laboring earth gravitation style air.Benefit from spillway irrigateand also air spillway can be arranged in such a way till work the pump canwork automatically and will labour on during balance constraint workthe pump not annoyed. From repair result got a technical age spillwaymount and stay more 6 month;moon and loss / water leakage causing tolessen the pressure can be avoided. To the condition of in such a way tillwork the pump automatically [done/conducted] a trial and error